Dampak Pembangunan Bendungan Tiga Dihaji Bagi Kehidupan Masyarakat Kecamatan Tiga Dihaji Kabupaten Oku Selatan - Aldi Wiranata; Ryllian Chandra Eka Viana; Najmi Muhammad Fadli (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
The construction of the Tiga Dihaji Dam, located in Tiga Dihaji District, South Ogan Komering Ulu Regency, is part of a National Strategic Project aimed at supporting irrigation and raw water provision, flood control, and regional economic development. This study aims to analyze the impact of the Tiga Dihaji Dam construction on community life and identify opportunities and benefits that can be utilized by affected communities. This research employed a descriptive qualitative approach, with data collection through field observations, in-depth interviews, and documentation. The results indicate that dam construction has positive impacts in the form of new job creation and increased community economic activity. However, it also has negative impacts, including loss of productive land, environmental damage, decreased discharge and quality of the Selabung River, and disruption to ecosystem balance and social order. This study uses Urip Santoso's Agrarian Politics Theory as an analytical framework to understand power relations between the state and society in infrastructure development. Sustainable social and environmental impact management policies, along with economic assistance and equitable compensation, are needed to optimally achieve development goals without sacrificing local community welfare.